Using Radar Plots to Demonstrate the Accuracy and Precision of 6 Blood Glucose Monitoring Systems. (September 2017) - Pardo, Scott; Dunne, Nancy; Simmons, David A.
Background: Previously, fingertip capillary blood glucose measurements from the CONTOUR ® NEXT (CN) blood glucose monitoring system (BGMS) and 5 other BGMSs were evaluated in comparison with measurements from a reference YSI glucose analyzer. Here, we use Radar Plots to graphically represent the accuracy and precision results from the previous study, including whether they met ISO 15197:2013 accuracy criteria. Method: A Radar Plot, a new method for capturing a distinct, single visualization of BGMS analytical performance, is a collection of concentric circles, each representing a particular magnitude of error. The center of the plot represents zero error (BGMS result is equivalent to reference result); as points are more distant from the center, the error increases, expressed in units of mg/dL or percentage for YSI values <100 and ≥100 mg/dL, respectively. The position of the data point above or below the horizontal line bisecting the plot indicates whether the BGMS measurement error was positive (BGMS result > YSI result) or negative (BGMS result < YSI result). Points within the "15-15 Zone, " representing ±15 mg/dL or ±15% error, satisfy ISO 15197:2013 accuracy criteria. Results: The percentage of results within the 15-15 Zone ranged from 83.6% to 99.8% for the 6 BGMSs (99.6% for CN). Conclusions: Radar Plots provide a different method for visually comparing the analytical performance of multiple BGMSs. The tight clustering of data points at the center of the CN Radar Plot illustrates the analytical performance of CN compared with 5 other BGMSs.